Implementation of Power BI for Dashboard Visualization on Brand Product Sales Dataset Adidas in the United States from Kaggle - Sulistyawati, Sri; Suyoso, Aldo Lovely Arief; Mardhiyah, Dien (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This article describes the implementation of Power BI to create an interactive dashboard based on a dataset of Adidas product sales in the United States from Kaggle. Power BI processes sales data to provide deep insights into sales trends, product performance, market analysis, and consumer preferences. The result is a clear and intuitive dashboard that assists management in strategic decision-making. This dashboard shows Total Sales of 899.90 million USD, Units Sold of 2 million units, and Operating Profit of 332.13 million USD, with the highest sales in New York, California, Florida, and Texas. Profitability analysis shows strong profit margins in New York and Florida, while the Men's Street Footwear product category is the top seller. This information is essential for identifying popular products and developing effective business strategies.